2010
DOI: 10.3109/0886022x.2010.516859
|View full text |Cite
|
Sign up to set email alerts
|

Study of urinary proteomes in Anderson-Fabry disease

Abstract: Background: Anderson-Fabry disease (AFD) is an X-linked genetic disorder with deficient a-galactosidase A activity. The main aim of this work was to investigate possible differences in urine proteins between healthy controls and AFD patients and to identify abnormal proteins as potential biomarkers of disease. Material and methods: We studied 2D electrophoresis images of urine samples collected from AFD patients and healthy subjects. The proteins were separated using isoelectric focusing method followed by SDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…Moore et al [18] compared serum samples of 12 male and 1 female pediatric Fabry patients before and after 6 months of ERT by LC-MS/MS and found 5 of 50 identified proteins to be significantly altered under therapy. Vojtova et al [19] compared 11 male and 9 female Fabry patients with or without ERT to 10 healthy controls using 2DGE followed by MALDI-TOF/TOF and identified 5 differentially expressed proteins. However, none of the above mentioned studies validated their results in an independent cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al [18] compared serum samples of 12 male and 1 female pediatric Fabry patients before and after 6 months of ERT by LC-MS/MS and found 5 of 50 identified proteins to be significantly altered under therapy. Vojtova et al [19] compared 11 male and 9 female Fabry patients with or without ERT to 10 healthy controls using 2DGE followed by MALDI-TOF/TOF and identified 5 differentially expressed proteins. However, none of the above mentioned studies validated their results in an independent cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, literature data indicate a higher urinary excretion of BTP in hypertensive patients, increasingly along with advance in renal dysfunction, in diabetic patients with subclinical renal injury or with cardiovascular complications, in lupus nephritis patients according to the activity of disease and efficacy of treatment, and also in Anderson–Fabry disease. [3643] …”
Section: Discussionmentioning
confidence: 99%
“…Vojtová et al found that the AFD does not lead to the formation of new proteins or degradation products, although quantitative changes were found in urine such as: substantially increased Ig kappa chain V-III, complement-C1q tumour necrosis factor-related protein and prostaglandin H2 d -isomerase [55]. …”
Section: Biomarkers and Imaging Findingsmentioning
confidence: 99%